Enhancing Students' Speaking Performance through Communicative Language Teaching (CLT) in the English Matriculation Program - Saputri, Faradillah; Rosalia, Harnita; Hasrul; Ratna (ENGLISH FRANCA : Academic Journal of English Language and Education, 2025)
This study addresses the challenge of improving English-speaking skills among Room Division students at Makassar Tourism Polytechnic, crucial for effective communication in hospitality roles. Many students struggle with fluency and confidence due to limited practice and language anxiety. To bridge this gap, the English Matriculation Program (EMP) was developed, integrating Communicative Language Teaching (CLT) to enhance practical language skills. A pre-experimental design was employed with 60 students, who underwent pre- and post-tests, alongside a questionnaire to gather perceptions of the program’s impact. Key CLT elements—social engagement, focus on meaning, and critical thinking—were emphasized, with tasks including role-plays and problem-solving exercises that mimic real-world communication. Structural equation modelling and paired t-tests indicated a significant improvement in speaking performance, with average scores rising from 39.10 to 62.87. Questionnaire results reinforced these findings, with students reporting increased confidence, reduced anxiety, and better fluency. Overall, CLT’s practical, student-centred approach effectively enhances English proficiency, preparing students for successful communication in the hospitality industry.